Protein-based nanofiltration coating loaded with nano-hydroxyapatite in situ as well as preparation method and application of protein-based nanofiltration coating
By loading nano-hydroxyapatite in situ in the protein-based nanofiltration coating, the problems of complex production processes and poor adsorption capacity of existing nanocomposite membranes are solved, and the effect of efficient uranium removal is achieved, and the advantages of simple preparation, low cost and environmental protection are provided.
Patent Information
- Application Number
- CN202411741060.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-01
AI Technical Summary
The existing nanocomposite films that adsorb uranium have complex production processes and poor adsorption capabilities. They are prone to precipitation during solution preparation, affecting the uniformity and stability of the film.
A protein-based nanofiltration coating with in situ loaded nanohydroxyapatite was used to form a white emulsion by adding (NH4)2HPO4 and Ca(NO3)2·4H2O to a protein-containing alkali solution to form a white emulsion, and dip it onto a polymer separation membrane, and dry it.
It achieves excellent removal performance of uranium within the pH range of 3.5-9.0, with an interception rate of more than 99.1%, a maximum adsorption capacity of up to 538.8 mg/g, and is simple in preparation, easy to produce on a large scale, and has the characteristics of low cost, low energy consumption, and environmental protection.
Smart Images

Figure CN119733490A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanofiltration coating technology, specifically to a protein-based nanofiltration coating with in-situ supported nano-hydroxyapatite, its preparation method, and its application. Background Technology
[0002] Given the ever-growing demand for environmentally friendly and efficient energy, nuclear energy has become an important option for many countries. This energy source, which replaces fossil fuels, does not produce greenhouse gases such as carbon dioxide and does not cause air pollution. Uranium is the most critical component in nuclear energy production. However, in many regions, wastewater from uranium mining may contain uranium concentrations exceeding the World Health Organization's limit of 30 micrograms per liter, posing a potential environmental pollution risk. Therefore, it is necessary to remove U(VI) from wastewater to protect the environment and the health of organisms.
[0003] In recent decades, researchers worldwide have explored various techniques for extracting or recovering uranium from seawater or uranium-containing wastewater, including coprecipitation, ion exchange, adsorption, and membrane filtration. Among these methods, adsorption is widely considered the most feasible due to its practicality, operability, cost-effectiveness, and environmental impact. Hydroxyapatite (HAP), a calcium phosphate mineral compound, exhibits superior uranium adsorption capacity compared to other inorganic adsorbents such as metal-organic frameworks, capable of adsorbing thousands of milligrams of uranium per gram (Fangdong Xie, Qile Fang, Yungui Li, Qingqing Li, Efficient removal of U(VI) by hydroxyapatite nanomaterials: Dependence on the phosphate release kinetics, Journal of Cleaner Production 2024, 469, 143180). However, in practical applications, the use of powdered HAP adsorbents can cause pipe blockage and necessitate solid-liquid separation after adsorption. Given this issue, many studies have loaded HAP into gels (patent application number 201510022179, Xiong, T., Li, Q., Liao, J., Zhang, Y., & Zhu, W. (2022). Highly enhanced adsorption performance to uranium (VI) by facile synthesized hydroxyapatiteaerogel. Journal of Hazardous Materials, 423, 127184.) and biochar (Kong, L., Ruan, Y., Zheng, Q., Su, M., Diao, Z., Chen, D., ... & Shih, K. (2020). Uranium extraction using hydroxyapatite recovered from phosphorus containing wastewater. Journal of Hazardous Materials, 382, 120784.) for uranium enrichment, but this method reduces the adsorption rate of HAP for uranium.
[0004] Membrane adsorption separation combines membrane separation and adsorption processes to achieve efficient removal and rapid enrichment of uranium. However, the primary method for loading hydroxyapatite onto membranes is physical mixing, which often leads to precipitation during solution preparation, resulting in uneven membrane thickness and easy detachment (Zhang, Y., Mei, B., Tian, X., Jia, L., & Zhu, W. (2023). Remediation of uranium(VI)-containing wastewater based on a novelgraphene oxide / hydroxyapatite membrane. Journal of Membrane Science, 675, 121543.). Biomimetic mineralization can produce uniform membranes, but current methods for biomineralizing hydroxyapatite onto membranes are typically complex and time-consuming, requiring hours or even days. For example, by modulating lysozyme, bovine serum albumin, silk, and β-lactoglobulin, self-assembled bio-based films can be formed, and a hydroxyapatite coating can be mineralized on the protein membrane (Patent Application No. CN201710507592). Furthermore, after mineralizing hydroxyapatite in biomass molecules (patent application number CN201710410839), there is a problem of solution instability and easy deposition, which is not conducive to the surface modification of the separation membrane.
[0005] Plant proteins have shown great potential as viable alternatives for producing protein-based membranes. These proteins are readily and sustainably available with minimal environmental impact. Among candidate proteins, soy protein isolate has been widely tested as a membrane-forming material due to its natural abundance as an agricultural byproduct. The self-assembly of nanostructured materials to prepare uranium-enriched separation membranes has been a research hotspot in the field of separation membranes in recent years. However, to date, most nanocomposite membranes with selective uranium adsorption capabilities cannot be mass-produced for industrial applications and exhibit poor adsorption performance. Summary of the Invention
[0006] To address the aforementioned technical problems, the present invention aims to provide a protein-based nanofiltration coating with in-situ supported nano-hydroxyapatite, its preparation method, and its application, thereby solving the problems of complex production processes and poor adsorption capacity of existing nanocomposite membranes for uranium adsorption.
[0007] The technical solution of the present invention to solve the above technical problems is as follows:
[0008] A method for preparing an in-situ supported hydroxyapatite protein-based nanofiltration coating includes the following steps:
[0009] (1) First, add (NH4)2HPO4 to the alkaline solution containing protein, and then mix and stir with Ca(NO3)2·4H2O solution to obtain a white emulsion;
[0010] (2) The white emulsion obtained in step (1) is dipped onto the polymer separation membrane and dried to obtain the product.
[0011] Further, in step (1), the alkaline solution is a sodium hydroxide solution with a concentration of 0.01-0.1 mol / L or a sodium carbonate solution with a concentration of 0.01-0.1 mol / L.
[0012] Furthermore, in step (1), the concentration of protein in the alkaline solution containing protein is 1-40 mg / mL, and the protein is soy protein isolate or corn protein.
[0013] Further, in step (1), the concentration of (NH4)2HPO4 after addition is 1-10 mg / mL; the mass ratio of (NH4)2HPO4 to Ca(NO3)2·4H2O is 0.5:1-1:3; and the concentration of Ca(NO3)2·4H2O solution is 3-40 mg / mL.
[0014] Furthermore, the mixing time in step (1) is 0.5-3 hours, and the temperature is 20-30℃.
[0015] Further, in step (2), the polymer separation membrane is any one of the following: polyamide membrane, polytetrafluoroethylene membrane, polypropylene membrane, polyethersulfone membrane, cellulose acetate membrane, and nuclear pore membrane with a pore size of 0.02-10 micrometers.
[0016] Furthermore, the drying temperature in step (2) is 70-90℃ and the time is 30-90min.
[0017] A protein-based nanofiltration coating with in-situ supported hydroxyapatite was prepared using the above-described method.
[0018] The above-mentioned in-situ loaded hydroxyapatite protein-based nanofiltration coating is used in the enrichment and separation of uranium in uranium-containing water.
[0019] The present invention has the following beneficial effects:
[0020] (1) In this invention, nano-hydroxyapatite is directly loaded in situ into a protein-based nanofiltration coating. The coating thickness is controllable, the membrane pore size is 1-2 nm, and it has good adhesion to the polymer membrane surface.
[0021] (2) The nanofiltration coating of the present invention exhibits excellent removal performance of uranium in the pH range of 3.5-9.0, with a rejection rate of more than 99.1% and a maximum adsorption capacity of up to 538.8 mg / g. In the presence of high concentrations of competing cations and anions, the nanofiltration coating exhibits excellent selectivity for uranium and a rejection rate of more than 90%.
[0022] (3) The preparation method of the present invention is simple and easy to achieve large-area preparation. At the same time, it has the characteristics of low cost, low energy consumption and environmental protection, avoiding the problems of complicated steps and environmental pollution in the chemical grafting process of traditional polymer separation membrane surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a transmission electron microscope image of the protein-based nanofiltration coating loaded with nano-hydroxyapatite in Example 1.
[0024] Figure 2 This is a scanning electron microscope image of the protein-based nanofiltration coating loaded with nano-hydroxyapatite in Example 1.
[0025] Figure 3 The adhesion strength of the protein-based nanofiltration coating loaded with nano-hydroxyapatite in Example 1;
[0026] Figure 4 The retention rate of uranium ions by the protein-based nanofiltration coating loaded with nano-hydroxyapatite in Example 1 in uranium ion solutions of different pH values.
[0027] Figure 5 The retention rate of uranium ions by the protein-based nanofiltration coating loaded with nano-hydroxyapatite in Example 1 in uranium ion solutions of different concentrations.
[0028] Figure 6 The retention rate of the protein-based nanofiltration coating loaded with nano-hydroxyapatite in Example 1 in a coexisting ion solution;
[0029] Figure 7 The rejection rate of uranium ions by the protein-based nanofiltration coating loaded with nano-hydroxyapatite in Example 1 in simulated seawater;
[0030] Figure 8 The retention rate of uranium ions by the protein-based nanofiltration coating loaded with nano-hydroxyapatite in simulated lake water in Example 1;
[0031] Figure 9 This is a reusability experiment of the protein-based nanofiltration coating loaded with nano-hydroxyapatite in Example 1;
[0032] Figure 10 This is a comparison of the uranium ion rejection rates of Example 1, Comparative Example 1, and the unmodified polyamide separation membrane;
[0033] Figure 11 The retention rates of uranium ions by protein-based nanofiltration coatings loaded with nano-hydroxyapatite prepared in Examples 2-4 are compared. Detailed Implementation
[0034] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not intended to limit the scope of the invention. In the embodiments, if specific conditions are not specified, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0035] Example 1:
[0036] A method for preparing an in-situ supported hydroxyapatite protein-based nanofiltration coating includes the following steps:
[0037] (1) At room temperature, 200 mg of soy protein isolate was dissolved in 10 mL of 0.05 mol / L sodium hydroxide aqueous solution to obtain a completely dissolved soy protein isolate alkaline solution.
[0038] (2) Add 0.0495g of (NH4)2HPO4 to the soybean protein isolate alkaline solution obtained in step (1) and dissolve it completely. Slowly add the resulting solution to 10mL of an aqueous solution containing 0.1476g of Ca(NO3)2·4H2O and stir magnetically for 2h to form a stable white emulsion.
[0039] (3) The white emulsion obtained in step (2) was dipped onto a polyamide separation membrane with a diameter of 5 cm and a pore size of 50 nm, and dried at 80 °C for 1 h. After drying, it was washed with deionized water to obtain a protein-based nanofiltration coating (PA-SPI / HAP) with in-situ loaded hydroxyapatite.
[0040] Example 2:
[0041] A method for preparing an in-situ supported hydroxyapatite protein-based nanofiltration coating includes the following steps:
[0042] (1) At room temperature, 100 mg of soy protein isolate was dissolved in 10 mL of 0.05 mol / L sodium hydroxide aqueous solution to obtain a completely dissolved soy protein isolate alkaline solution.
[0043] (2) Add 0.0495g of (NH4)2HPO4 to the soybean protein isolate alkaline solution obtained in step (1) and dissolve it completely. Slowly add the resulting solution to 10mL of an aqueous solution containing 0.1476g of Ca(NO3)2·4H2O and stir magnetically for 2h to form a stable white emulsion.
[0044] (3) The white emulsion obtained in step (2) is dipped onto a polyamide separation membrane with a diameter of 5 cm and a pore size of 50 nm, and dried at 80 °C for 1 h. After washing with deionized water, a protein-based nanofiltration coating with in-situ loaded hydroxyapatite is obtained.
[0045] Example 3:
[0046] A method for preparing an in-situ supported hydroxyapatite protein-based nanofiltration coating includes the following steps:
[0047] (1) At room temperature, 200 mg of soy protein isolate was dissolved in 10 mL of 0.01 mol / L sodium hydroxide aqueous solution to obtain a completely dissolved soy protein isolate alkaline solution.
[0048] (2) Add 0.0495g of (NH4)2HPO4 to the soybean protein isolate alkaline solution obtained in step (1) and dissolve it completely. Slowly add the resulting solution to 10mL of an aqueous solution containing 0.1476g of Ca(NO3)2·4H2O and stir magnetically for 2h to form a stable white emulsion.
[0049] (3) The white emulsion obtained in step (2) is dipped onto a polyamide separation membrane with a diameter of 5 cm and a pore size of 50 nm, and dried at 80 °C for 1 h. After washing with deionized water, a protein-based nanofiltration coating with in-situ loaded hydroxyapatite is obtained.
[0050] Example 4:
[0051] A method for preparing an in-situ supported hydroxyapatite protein-based nanofiltration coating includes the following steps:
[0052] (1) At room temperature, 200 mg of soy protein isolate was dissolved in 10 mL of 0.05 mol / L sodium carbonate aqueous solution to obtain a completely dissolved soy protein isolate alkaline solution.
[0053] (2) Add 0.0495g of (NH4)2HPO4 to the soybean protein isolate alkaline solution obtained in step (1) and dissolve it completely. Slowly add the resulting solution to 10mL of aqueous solution containing 0.1476g of Ca(NO3)2·4H2O and stir magnetically for 2h to form a stable white emulsion.
[0054] (3) The white emulsion obtained in step (2) is dipped onto a polyamide separation membrane with a diameter of 5 cm and a pore size of 50 nm, and dried at 80 °C for 1 h. After washing with deionized water, a protein-based nanofiltration coating with in-situ loaded hydroxyapatite is obtained.
[0055] Comparative Example 1:
[0056] A method for preparing a protein-based nanofiltration coating includes the following steps:
[0057] (1) At room temperature, 200 mg of soy protein isolate was dissolved in 10 mL of 0.05 mol / L sodium hydroxide aqueous solution to obtain a completely dissolved soy protein isolate alkaline solution.
[0058] (2) The soybean protein isolate alkaline solution obtained in step (1) is dipped onto a polyamide separation membrane with a diameter of 5 cm and a pore size of 50 nm, and dried at 80 °C for 1 h. After washing with deionized water, a protein-based nanofiltration coating is obtained.
[0059] Experimental Example 1: Morphology and Adhesion Strength Characterization
[0060] The protein-based nanofiltration coating with in-situ hydroxyapatite loaded in Example 1 was characterized using transmission electron microscopy, scanning electron microscopy, and a pull-out adhesion tester.
[0061] Experimental results are as follows Figure 1-Figure 3 As shown. Transmission electron microscopy results show that hydroxyapatite consists of rod-shaped nanoparticles (…). Figure 1 Scanning electron microscopy results showed that the porous fiber structure was completely covered after the protein membrane was loaded onto the polyamide membrane, and the membrane surface was smooth and dense. The coating adhesion strength characterization results showed that the adhesion force of the prepared nanofiltration coating on the polymer membrane surface was 0.20-0.25 MPa, which has good adhesion force and is beneficial to its stability during use.
[0062] Experimental Example 2: Effects of pH, uranium ion concentration, and coexisting ions on membrane separation performance
[0063] The protein-based nanofiltration coating with in-situ supported hydroxyapatite prepared in Example 1 was used for experiments.
[0064] (1) Effect of pH on membrane separation performance
[0065] The pH of the 25 mg / L uranium ion aqueous solution was adjusted to 2–10. Then, the protein-based nanofiltration coating (PA-SPI / HAP) with in-situ supported hydroxyapatite prepared in Example 1 was installed in a membrane separation device. Uranium ion aqueous solutions with different pH values were separated by vacuum filtration at 100 kPa. The concentration of the solution after filtration was detected by ICP-OES.
[0066] Experimental results are as follows Figure 4 As shown, PA-SPI / HAP exhibits excellent uranium removal performance in the pH range of 3.5-9.0, with a retention rate greater than 99.1%.
[0067] Meanwhile, the PA-SPI / HAP prepared by this invention was compared with the material prepared by patent application number CN201710507592 (a hydroxyapatite / phase transition lysozyme coating hybrid material and its preparation method) for uranium separation. The results showed that the coating prepared by this invention had a higher uranium removal rate under acidic conditions, with the removal rate increased by 15%. The main reason is that soy protein isolate itself is insoluble under these acidic conditions, while the in-situ loading of hydroxyapatite forms a layer of soy protein isolate molecules on the surface of the nano-hydroxyapatite, which increases the acid resistance of the coating.
[0068] (2) Effect of uranium ion concentration on membrane separation performance
[0069] The pH of uranium ion aqueous solutions ranging from 1 to 1000 mg / L was adjusted to 4. Then, the PA-SPI / HAP prepared in Example 1 was installed in a membrane separation device. Uranium ion aqueous solutions of different concentrations were separated by vacuum filtration at 100 kPa. The concentration of the solution after filtration was detected by ICP-OES.
[0070] Experimental results are as follows Figure 5 As shown, when the concentration is below 250 mg / L, the coating prepared by the present invention has a uranium ion rejection rate of over 90%. As the concentration continues to increase, the rejection rate gradually decreases. The maximum saturated adsorption capacity of the nanofiltration coating prepared by the present invention for uranium is 538.8 mg / g.
[0071] (3) The effect of coexisting ions on uranium ion separation performance
[0072] K + 、Na + Mg 2+ Ca 2+ Cl - NO3 - CO3 2 and SO4 2- These are cations and anions commonly found in natural water or wastewater. This invention selects these ions as typical coexisting ions to determine the performance of the PA-SPI / HAP separation membrane in removing uranium. The PA-SPI / HAP prepared in Example 1 was used as the experimental object. It was installed in a membrane separation device, and the aqueous solution containing uranium ions containing different coexisting ions was separated by vacuum filtration at 100 kPa. The concentration of the solution after filtration was detected by ICP-OES.
[0073] Experimental results are as follows Figure 6 As shown, the membrane exhibits better uranium separation performance regardless of whether coexisting ions are present in the solution.
[0074] Experimental Example 3: Simulating Uranium Enrichment Performance in Seawater
[0075] The simulated seawater contained 193 mg / L NaHCO3, 25600 mg / L NaCl, 120 mg / L MgCl2, 60 mg / L CaCl2, and 30 μg / L uranium ions. The PA-SPI / HAP solution prepared in Example 1 was installed in a membrane separation device, and the simulated seawater was separated by vacuum filtration at 100 kPa. The concentration of the solution after filtration was detected by ICP-OES.
[0076] Experimental results are as follows Figure 7 As shown, the results indicate that the PA-SPI / HAP prepared in Example 1 of this invention has a uranium rejection rate of greater than 98%.
[0077] Experiment Example 4: Simulating the uranium enrichment performance in salt lake water
[0078] The simulated salt lake water had a uranium ion concentration of 300 μg / L and an Mg / Li ratio of 30, i.e., C Mg =90g / L, C Li =3 g / L. The PA-SPI / HAP prepared in Example 1 was installed in a membrane separation device, and simulated lake water was separated by vacuum filtration at 100 kPa. The concentration of the solution after filtration was detected by ICP-OES.
[0079] Experimental results are as follows Figure 8 As shown, the results indicate that the PA-SPI / HAP prepared in Example 1 of this invention has a uranium rejection rate of greater than 94%.
[0080] Experimental Example 5: Desorption-Adsorption Experiment
[0081] Uranium bound to uranium was eluted from the separation membrane after uranium ion filtration using a sodium carbonate-hydrogen peroxide desorption solution (0.1 mol / L Na₂CO₃, 0.1 mol / L H₂O₂). The membrane was immersed in the desorption solution and gently shaken for 12 h. The concentration of uranium ions in the solution was measured by ICP-OES. The membrane was then subjected to uranium separation experiments again. The desorption-adsorption process was repeated 5 times. The experimental sample was the PA-SPI / HAP prepared in Example 1.
[0082] Experimental results are as follows Figure 9 As shown, the results indicate that the uranium retention rate remained above 90% even after five adsorption-desorption cycles.
[0083] Experimental Example 6: Uranium Removal Performance of Different Coatings
[0084] The uranium removal performance of the in-situ hydroxyapatite-supported protein-based nanofiltration coatings prepared in Examples 1-4 and the protein-based nanofiltration coating prepared in Comparative Example 1 was tested, with an unmodified polyamide separation membrane (50 nm pore size) used as a blank control. The uranium ion aqueous solution was a single uranium ion aqueous solution with a uranium ion concentration of 25 mg / L and a pH of 5. The separation performance of different membranes was tested by vacuum filtration at 100 kPa, and the solution concentration after filtration was determined by ICP-OES.
[0085] Experimental results are as follows Figure 10 and Figure 11 As shown.
[0086] like Figure 10 As shown, the unmodified polyamide separation membrane had a uranium ion rejection rate of only 2.3%, while the separation membrane with only soy protein isolate coating prepared in Comparative Example 1 had a uranium ion rejection rate of 70%, and the PA-SPI / HAP prepared in Example 1 achieved a uranium ion rejection rate of 98%. It was also found that the protein-based nanofiltration coating prepared in Comparative Example 1 was very fragile after preparation, which is not conducive to practical applications.
[0087] like Figure 11 As shown, the protein-based nanofiltration coatings with in-situ supported hydroxyapatite prepared in Examples 2-4 of this invention all have a uranium ion rejection rate of over 90%. The main reason is that the synergistic effect of membrane pore size sieving and HAP adsorption of uranium is combined during the uranium ion removal process.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a protein-based nanofiltration coating loaded with hydroxyapatite in situ, characterized in that: The following steps are involved: (1) First, add (NH4)2HPO4 to the protein-containing alkaline solution, and then mix and stir with Ca(NO3)2·4H2O solution to obtain a white emulsion; (2) The white emulsion obtained in step (1) is dip-coated on a polymer separation membrane and dried to obtain a separation membrane.
2. The method for preparing the protein-based nanofiltration coating with in-situ hydroxyapatite loading according to claim 1, characterized in that: The alkaline solution in step (1) is a sodium hydroxide solution with a concentration of 0.01-0.1 mol / L or a sodium carbonate solution with a concentration of 0.01-0.1 mol / L.
3. The method for preparing the protein-based nanofiltration coating with in-situ hydroxyapatite loading according to claim 1, characterized in that: The protein concentration in the protein-containing alkaline solution in step (1) is 1-40 mg / mL, and the protein is soy protein isolate or corn protein.
4. The method for preparing the protein-based nanofiltration coating with in-situ hydroxyapatite loading according to claim 1, characterized in that: In the step (1), the concentration of (NH4)2HPO4 after addition is 1-10 mg / mL; the mass ratio of (NH4)2HPO4 and Ca(NO3)2·4H2O is 0.5:1-1:3; the concentration of the Ca(NO3)2·4H2O solution is 3-40 mg / mL.
5. The method for preparing the protein-based nanofiltration coating with in-situ hydroxyapatite loading according to claim 1, characterized in that: The mixing and stirring time in step (1) is 0.5-3h, and the temperature is 20-30°C.
6. The method for preparing the protein-based nanofiltration coating with in-situ hydroxyapatite loading according to claim 1, characterized in that: The polymer separation membrane in step (2) is any one of polyamide membrane, polytetrafluoroethylene membrane, polypropylene membrane, polyethersulfone membrane, cellulose acetate membrane and nuclear pore membrane with a pore size of 0.02-10 microns.
7. The method for preparing the protein-based nanofiltration coating with in-situ hydroxyapatite loading according to claim 1, characterized in that: The drying temperature in step (2) is 70-90° C. and the drying time is 30-90 min.
8. A protein-based nanofiltration coating loaded with hydroxyapatite in situ, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the protein-based nanofiltration coating with in-situ hydroxyapatite loading according to claim 8 in enriching and separating uranium in uranium-containing water.
Citation Information
Patent Citations
Material capable of enriching and separating uranium in water solution and preparation method of material
CN104587982A
A hydroxyapatite / phase transition lysozyme coating hybrid material and its preparation method
CN107115565B
Preparation method of hybridized hydroxyapatite porous material and application thereof
CN107185500A